WEB BASED ARCHIVE MANAGEMENT APPLICATION CASE STUDY IN CIJERAH VILLAGE (E-ARCHIVE) - Cahyati, Sri (Politeknik Siber Cerdika Internasional, 2024)
This research has the goal of producing a mathematics learning medium in which the game contains mathematical material, namely matrix material which is designed with various challenges, questions, and in-game events related to the matrix. The research method used is the research and development method. The research procedure is a simplification of Sugiyono's development steps, namely potentials and problems, data collection, product design, design validation, design improvement, product trials, product revisions, usage trials, and conclusions. The results of the study show that educational game media has proper characteristics. This can be seen from the evaluation of the experts, media experts obtained a proportion of 86.7% with a proper rating and material experts obtained a proportion of 88.3% with the assessment criteria, and math teachers of 90.85% with the appropriate assessment criteria. Contribution of the research is that this educational game media can be used by teachers in the learning process for matrix materials. This helps the teacher so that the learning process is more practical because the material is packaged in a game. In addition, this educational game media can also help students learn independently.